Lipid Level of Street Food at Cibeusi Elementary School in Jatinangor Subdistrict, West Java, Indonesia - Siti Nur Fatimah; Indri Nurul Hayyi; Adria Adnan (Faculty of Medicine Universitas Padjadjaran, 2020)
Background: School-aged children have quite high energy consumption demand because they are growing and physically active. In Indonesia, school-aged children frequently consume their additional foods/snacks from street food vendors around their schools. This study aimed to reveal the lipid level of street food in Elementary Schools, in Jatinangor Subdistrict, West Java, Indonesia.Methods: This study was an observational descriptive study. Elementary Schools in Jatinangor Subdistrict were selected using a random sampling method. Four frequent street foods were fried meatball (in Indonesian: bakso goreng (basreng)), batagor (bakso tahu goreng), crepes, and egg roll were then taken, and lipid level was measured twice using Soxhlet extraction method.Results: Fried meatball contained 22.10% (±0.23%) or 2.78 gram lipid, batagor 30.091% (±4.14%) or 12.49 gram lipid, crepes 7.14% (± 0.12%) or 0.66 gram lipid, and egg roll 13.66% (±1.63%) or 1.28 gram lipid.Conclusions: Only the batagor fulfilled the lipid demand in one snack time. It is recommended to minimize the intake of batagor as a between-meal snack for a balanced nutrient intake control.